The Belarusian-German relations: key factors of influence - Sharapo, Aliaksandr V. (Journal of the Belarusian State University. International Relations, 2019)
The article considers political, economic and ideological factors of influence on the Belarusian-German relations. The author identifies such events of the late 20th – early 21st centuries as the collapse of the Soviet Union and the formation of independent states in the post-Soviet space, the unification of Germany, the formation and expansion of the EU as political factors. Special emphasis is placed on the differences between the Belarusian-German relations before and after 1994 and the importance of the internal political situation in Belarus in this regard. The author contrasts the position of Germany on this issue in the first years of independence and after the election of President Alexander Lukashenko, when the issues of human rights and democracy were put forward by Germany as a condition for expanding political cooperation between our countries. Much attention is paid to the argumentation of the thesis on the dependence of the foreign policy of Germany, including bilateral relations with Belarus, on the consolidated policy of the European Union. It is emphasized that despite the demonstration of independence in determining the nature of the Belarusian-German relations, Germany often supported the anti-Belarusian EU resolutions under far-fetched pretexts. At the same time, economic ties between Belarus and Germany are singled out as a positive factor. A number of statistical data confirming the overall positive dynamics of their development are given. However, a more comprehensive comparative analysis of exports and imports shows periodic declines in economic cooperation. One of the reasons the author calls the aggravation of the political and economic situation in Germany. In this regard, he notes the presence of ideological factors of influence, in particular, the growth in the Federal Republic of Germany of extreme right wing and rightleftsentiments, populism in party programs and the decline in the popularity of leading parties.
Keywords: Belarus; Germany; political, economic and ideological factors; the European Union; electorate; political parties of the Federal Republic of Germany